The particularities of aviation accidents investigations involving military aircrafts - Ichim-Codrin SÎRCU (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
When exceptional situations occur (calamities, armed conflicts, pandemics, etc.), an important resource used for their management is represented by military aircrafts. Their complexity and the complexity of the missions they perform are extremely high, which induces a complexity similar to the on-site investigation in the case of aviation accidents involving aircrafts of this category. This article, without claiming to be exhaustive on the subject, aims to identify, starting from the study of several criminal cases definitively resolved by the military prosecutors' offices in Romania in the period 1990-2023, the most important particularities of this multipurpose evidentiary procedure, with the aim of understanding the main forensic challenges that investigators face in trying to find out the truth when handling such cases.